Gnostic and agnostic immunotherapy by tropism-retargeted herpes simplex virus without direct tumor treatment - Andrea Vannini; Federico Parenti; Cristina Forghieri; Elisabetta Romagnoli; Daniela Massaro; Anna Zaghini; Gabriella Campadelli-Fiume; Tatiana Gianni (Journal for ImmunoTherapy of Cancer)
Background Cancer immunotherapy includes vaccines generated through distinct approaches, each with advantages and limitations. Those made of autologous or allogeneic whole cells do not require prior identification of antigens, that is, immunize against undetermined (agnostic) tumor antigens. However, they often exhibit low adjuvanticity and modest antigenicity. Viruses have emerged as elicitors and enhancers of immune responses. Oncolytic viruses are replicating anticancer agents, most often administered intratumorally. They derepress the immunosuppressive tumor microenvironment through different mechanisms, and some promote antitumor immunity—a strategy termed oncolytic immunotherapy. Tropism-retargeted oncolytic herpes simplex viruses (here ReHVs), generated in our laboratory, specifically target a tumor-associated antigen (TAA) of choice that serves as receptor for ReHV entry into the cancer cell. ReHVs do not cause off-target infections in preclinical models, are fully replication-competent and able to contrast the antiviral innate responses they elicit, and prime T cells against tumors.Methods We developed an ReHV-mediated immunotherapeutic platform (Re-IP) that consists of thymidine kinase-positive cancer cells ex vivo infected with ad hoc designed HER2-tropic ReHV implanted ectopically to immunize mice against cancer without direct tumor treatment.Results In a therapeutic-like setting, Re-IP robustly primed anticancer T cells that infiltrated distant untreated tumors and inhibited their growth. Tumor growth inhibition required CD8+ cells. Re-IP vaccinated against both the gnostic TAA (here HER2) employed for ReHV retargeting and a broader repertoire of agnostic tumor antigens, also sensitizing tumors to checkpoint blockade. Ectopically implanted uninfected cancer cells failed to elicit an immune response, highlighting the adjuvant effect of ReHV infection. Re-IP was effective in herpes simplex virus (HSV)-preimmune mice, unlike systemic treatments with oncolytic HSVs, which are blunted by prior antiviral immunity. Re-IP safety rested in the absence of replicating virus in off-target tissues and in tumors whose growth was inhibited.Conclusions Ectopically administered Re-IP adjuvants cancer cells’ immunogenicity without the need for direct tumor treatment. The induced T-cell immunity inhibits the growth of distant untreated tumors and remains effective in HSV-preimmune mice. In humans, this approach might be applied to elicit anticancer T-cell responses against hard-to-reach, unresectable, or metastatic lesions and to enhance immune cell activation and expansion in adoptive therapies.